The Use of Analog and Digital Games for Autism Interventions - Atherton, Gray; Cross, Liam (Frontiers in Psychology, 2021)
Many interventions that target improvements in social communication and other cognitive, learning, and physical issues have been developed to help autistic people. The gamification of interventions offers an alternative approach to fostering and assessing desired behaviors and cognitions in a more naturalistic and emergent setting. In this scoping review aimed at educators, practitioners, and parents of those with autism, we detail studies that have tested game-based approaches to improving the lives of autistic children, adolescents, and adults, focusing on how research into gamification and autism can both progress and can be progressed and implemented. We offer parents, professionals and academics resources to incorporate game-based psycho-educational programs into their current practice.